Fruits and vegetables that are sources for lutein and zeaxanthin: the macular pigment in human eyes. Issue 8 (1st August 1998) - Sommerburg, Olaf; Keunen, Jan E E; Bird, Alan C; van Kuijk, Frederik J G M
Abstract : BACKGROUND: It has been suggested that eating green leafy vegetables, which are rich in lutein and zeaxanthin, may decrease the risk for age related macular degeneration. The goal of this study was to analyse various fruits and vegetables to establish which ones contain lutein and/or zeaxanthin and can serve as possible dietary supplements for these carotenoids. METHODS: Homogenates of 33 fruits and vegetables, two fruit juices, and egg yolk were used for extraction of the carotenoids with hexane. Measurement of the different carotenoids and their isomers was carried out by high performance liquid chromatography using a single column with an isocratic run, and a diode array detector. RESULTS: Egg yolk and maize (corn) contained the highest mole percentage (% of total) of lutein and zeaxanthin (more than 85% of the total carotenoids). Maize was the vegetable with the highest quantity of lutein (60% of total) and orange pepper was the vegetable with the highest amount of zeaxanthin (37% of total). Substantial amounts of lutein and zeaxanthin (30–50%) were also present in kiwi fruit, grapes, spinach, orange juice, zucchini (or vegetable marrow), and different kinds of squash. The results show that there are fruits and vegetables of various colours with a relatively high content of lutein and zeaxanthin. CONCLUSIONS: Most of the dark green leafy vegetables, previously recommended for a higher intake of lutein and zeaxanthin, have 15–47% of lutein, but a very low content (0–3%) of zeaxanthin. Our study shows that fruits and vegetables of various colours can be consumed to increase dietary intake of lutein and zeaxanthin.